PROMOTIONAL EFFORTS IN INCREASING TOURIST VISITS (CASE STUDY OF SANROBENGI ISLAND TOURISM OBJECT) - Yuliani, Nur Fadny; Rachman, Siswati (Jurnal Ekonomi Balance, 2020)
This research was conducted in Sanrobengi Island, Boddia Village, Takalar Regency with the aim of knowing promotional efforts to increase tourist visits in Sanrobengi Island.In this study, data collection techniques were used, including: Observation, Interview (interview), Documents and Documentation. This type of research uses qualitative data with a qualitative descriptive analysis method. The results of this study indicate that efforts to promote tourism objects in sanrobengi island in increasing tourist visits are: 1. Advertising 2. Sales Promotion 3. Public Relations 4. Word of Mouth Marketing ( WoMM) 5. Direct Marketing (Direct Marketing). There are factors that support and hinder efforts to promote tourism objects in Sanrobengi Island in an effort to increase tourist visits from internal and external sources. Promotion and marketing have an important role in introducing the Sanrobengi Island tourist attraction to the wider community. Besides that, it also serves to increase income for the Sanrobengi Island tourist attraction.